Clinical Features of Apert Syndrome in Infancy: A rare case in Indonesia - Mapindra, Muhammad Pradhika; Mahindra, Muhammad Pradhiki (SCRIPTA SCORE Scientific Medical Journal, 2021)
Background: Apert syndrome is characterized by several malformations of cranial-facial and syndactyly. The incidence of Apert syndrome was reported at approximately 1 per 65,000 live births, globally. Fibroblast Growth Factor 2 (FGFR2) is believed to hold a key role in the syndrome. Objectives: This case report is aiming to describe the information on a rare incidence of craniosynostosis syndromes on Indonesian infants. Case Illustration: One month old female baby was admitted to the hospital due to the breastfeeding difficulty caused by cleft palate. The patient was known to experience defects of face-head features and syndactyly since birth. This patient was observed and controlled to undergo nasogastric feeding until meet the appropriate age for surgical therapy. Discussion: Mutation ofÂ  Ser252Trp and Pro253Arg was found in the patient. Based on this finding, this case report may strengthen the statement about the correlation between Ser252Trp and cleft palate whereas Pro253Arg is linked with syndactyly in individuals with the syndrome. Conclusion:. This case may give beneficial information for clinicians when they receive a patient with the same clinical features. However, further investigation to know this syndrome still needs to be developed. Keywords: Apert Syndrome, FGFR2, palate cleft, Pro253Arg, Ser252Trp Â  Latar Belakang: Pasien dengan sindroma Apert memiliki fitur karakteristik berupa malformasi kepala dan wajah disertai syndactyly. Insidensi sindroma ini berkisar 1 per 65.000 kelahiran hidup secara global. Etiologi kelainan ini dikatikan dengna mutase pada Fibroblast Growth Factor 2 (FGFR2). Tujuan: Laporan kasus ini bertujuan untuk mendeskripsikan kejadian langka dari sindroma craniosynostosis pada bayi Indonesia. Ilustrasi Kasus: Bayi perempuan usia 1 bulan dibawa ke rumah sakit dengan masalah menyusui akibat palatoschizis. Pasien memiliki riwayat defek wajah dan kepala disertai syndactyly sejak lahir. Pasien ini kemudian diobservasi melalui diet per nasogastric tube sampai siap dilakukan terapi pembedahan. Pembahasan: Mutasi pada Ser252Trp dan Pro253Arg ditemukan pada pasien ini. Sehingga, laporan kasus ini mungkin memperkuat temuan mengenai korelasi Ser252Trp dan palatoschizis sedangkan Pro253Arg dikaitkan dengan syndactyly. Kesimpulan: Kasus ini mungkin dapat memberikan informasi tambahan sebagai referensi untuk klinisi ketika menerima pasien dengan gejala klinis serupa. Namun, studi terkait perlu diperdalam untuk mengetahui lebih jauh mengenai sindroma serupa. Kata Kunci: FGFR2, palatoschizis, Pro253Arg, Ser252Trp, sindroma Apert